Effect of intramolecular charge transfer processes on amplified spontaneous emission of D–π–A type aggregation-enhanced emission molecules. Issue 9 (20th February 2023) - Li, Yuanzhao; Han, Pengbo; Zhang, Xiaowei; Zhou, Jiadong; Qiao, Xianfeng; Yang, Dezhi; Qin, Anjun; Tang, Ben Zhong; Peng, Junbiao; Ma, Dongge
Abstract : The intensity of the ICT process in D–π–A molecules directly affects ASE properties by modulating the energy bandgaps. Suppressing the ICT process by physical doping or incorporating steric groups can effectively enhance the ASE performances. Abstract : The intramolecular charge transfer (ICT) process exists widely in lasing molecules which contain electron donors and acceptors. These types of polar molecules are advantageous for securing the charge carrier transport balance that is significant for achieving electrically pumped organic semiconductor lasers (EPOSLs). Therefore, a good understanding of how the ICT process affects the stimulated emission is helpful to develop efficient organic gain materials for applications in EPOSLs. Here, the amplified spontaneous emission (ASE) properties of two donor–π–acceptor type aggregation-enhanced emission (AEE) luminogens (2PB-AC and TPB-AC) were investigated using both steady-state and transient photoluminescence spectroscopy as well as femtosecond transient absorption spectra analysis. The ICT process for polar molecules is sensitive to the distance of the adjacent molecule, which induced the properties of spontaneous emission and stimulated emission to show a concentration dependence. With the enhancement of the ICT process, the overlap between the emission and excited state absorption spectra is enlarged, and the ASE threshold also increases. It is shown that the physical doping or introducing steric groups into molecules can effectively guarantee mirror symmetry between the stimulated emission and emission spectra and reduce the ASE threshold, providing a new idea for the design of efficient lasing organic molecules.